Three essays on corporate finance - Zhang, Wenrui (2012)
Essay one examines the disciplinary role of corporate pension deficits (the difference in value between pension liabilities and pension assets) in the market for corporate control. We find that during the 1981 to 2008 period, firms with larger pension deficits are less likely to engage in mergers and acquisitions (M&As), particularly diversifying M&As, than those with smaller or no pension deficits. We also find that the announcement returns of both the acquirer and the value-weighted portfolio of the acquirer and the target increase with acquirers’ pension deficits. Further, acquirers’ pension deficits are negatively related to the premiums paid to targets, but positively related to the percentage of cash used in payment to targets. These results are evident only for a subsample of financially unconstrained acquirers, suggesting that they are not driven by lack of acquirers’ internal funds. The results are also more pronounced for subsamples of acquirers whose pension plans are dominated by actively working employees (i.e., fewer retirees), those whose pension plans are collectively bargained, and those in more unionized industries. These findings indicate that corporate pension deficits provide employees with strong incentives to monitor managerial performance and influence managers to make value-enhancing investment decisions.